Implementation of adolescent health programs at public schools and religion-based schools in Indonesia - Muthmainnah Muthmainnah; Ira Nurmala; Pulung Siswantara; Riris Diana Rachmayanti (SAGE Publishing, 2021)
Background: Adolescents are a vulnerable group who have great curiosity and need access to various adolescent health information. Therefore, the government has implemented a strategy through the implementation of Youth Care Health Services (YCHS). However, some of the stakeholders and youth have limited access to YCHS especially the ones delivered in schools setting. The purpose of this study was to investigate the implementation of adolescent health programs in schools especially public schools and religion-based schools. Design and methods: This study was an analytic observational quantitative study by using a cross-sectional design.This study was conducted in public schools and religion-based schools in North Surabaya Indonesia. The sample in this study consisted of 100 students through a simple random sampling technique. Results: There was a difference in the level of knowledge of adolescent reproductive health between public schools and religion-based schools (p=0,047). Student's attitudes (p=0,000) and environmental influences (p=0,000) both related with reproductive health contents. However, there was no difference in adolescent's attitudes about adolescent reproductive health programs (p=0,190) and adolescent's exposure to adolescent reproductive health policies (p=0,196). Conclusion: The implementation of adolescent health programs in two types of schools (public and religion-based) were different. Adolescents should have the same rights to obtain knowledge about adolescent health as the prelude for forming a positive attitude. Therefore, stakeholders need to conduct regular monitoring and evaluation on the implementation of standardized adolescent health programs in all types of schools.